Pergeseran Isu Gender dalam Persepktif Hukum yang Hidup dalam Masyarakat Bali - I Kadek Agus Aditya Firmantara; I Gede Pasek Pramana (LP3M Sekolah Tinggi Ilmu Hukum Al-Banna, 2025)
This study aims to analyze the shifting gender issues from the perspective of the living law in Balinese society, particularly within the context of transforming customary norms and the evolving role of women in the social structure of the desa adat (customary village). Balinese customary law, as a form of living law rooted in local values and Balinese Hindu spirituality, essentially regulates social relations in a hierarchical and communal manner. However, modern social dynamics, educational development, and the penetration of global equality values have led to a fundamental change in society’s perception of gender roles. This research employs a normative legal method using conceptual and statutory approaches. Legal materials are obtained through a literature review of customary law sources, awig-awig (village customary regulations), and relevant statutory instruments, and are analyzed qualitatively. The findings indicate that the shift in gender issues within Balinese society is not merely triggered by external pressures of modernity but also represents a process of reinterpretation of traditional values by the customary community itself. The principle of balance (Rwa Bhineda), which forms the philosophical foundation of Balinese customary law, has begun to be actualized to create more equitable social relations between men and women. The living law within Balinese society demonstrates adaptive flexibility toward the value of gender equality without abandoning its cultural and spiritual roots.